DESCRIPTION OF THE RESULT OF THE EXAMINATION OF PAP SMEAR AFTER RADIATION THERAPY ON CERVICAL CANCER PATIENTS BASED ON THE TYPE OF CELL AT ARIFIN ACHMAD GENERAL HOSPITAL PEKANBARU IN THE PERIOD 2009-2013 - Trigen Yulis Rahmat Yulis; Amru Sofian; Mardhiah Gaffar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cervical cancer is the second most for women in the world. Cervical cancer most often found in advanced stage. The main therapy for advanced stage cervical cancer is radiation therapy. Radiation is also used as therapy for early stage of cervical cancer patient who is not eligible for surgery. Radiation is divided into two, externa radiation and internal radiation. In RSUD Arifin Achmad Pekanbaru is only using externa radiation caused by limitation of the tools on interna radiation. After the complete radiation, patients will do pap smear as follow up to analyse the cell cancer. This research has been done in Radiotherapy Installation, Pathology Anatomic Installation, and Medical Record Installation in RSUD Arifin Achmad. This research uses a descriptive retrospective design by taking a patient's medical record of cervical cancer in RSUD Arifin Achmad period 2009-2013. The result showed that squamous cell carcinoma is the most histhopathology in cervical cancer. 30 of 78 cervical cancer patients who had been in radiation therapy continue to follow up pap smear. The result of pap smear test showed that there are non-malignant cell in 26 patients and the type of cell is squamous cell carcinoma and adenocarcinoma in 2 patients. And in 2 adenocarcinoma patient is found malignant cells. There is a cervical cancer patient with squamosa cell carcinoma who experienced recurrence at 7-9 months after radiation.Keyword : cervical cancer, radiation, pap smear